Implementing a Deep Learning Pedagogical Approach in Social Studies to Improve Elementary Students' Social Skills - Dian Purnomo; Rohani Rohani; Yasnel Yasnel; Fanny Suci Fadillah; Dessy Syofiyanti (MASI Mandiri Edukasi, 2026)
Elementary education requires learning that develops both academic understanding and students' social competence. Social Studies learning in elementary and madrasah settings remains largely teacher-centered and has not optimally developed social skills. Empirical studies integrating Social Studies, Deep Learning pedagogy, and Dikdasmen Graduate Profile are still limited. This study examines the design and implementation of Deep Learning-based Social Studies learning to support students' social competence. A mixed methods exploratory sequential design involved one Grade V teacher and 24 students at MIN 1 Indragiri Hulu. Data were collected through observation, interviews, questionnaires, documentation, and social competence instruments. Quantitative analysis used descriptive statistics and the Wilcoxon test. Results show contextual, collaborative, reflective, and project-based learning with high social competence (M = 83.72). The Wilcoxon test indicated a significant difference from the criterion (p < 0.001) and a strong effect size (r = 0.71). Findings indicate students' scores exceeded the expected standard, suggesting strong outcomes rather than pre–post improvement. The study provides implications for strengthening assessment rubrics, reflective practices, and teacher facilitation in Social Studies.